A mmWave Transmitting Time Modulated Array Using Bespoke GaAs Integrated Circuits—Prototype Design and Laboratory Trials at 73 GHz - Edward A. Ball; Sumin David Joseph (IEEE Open Journal of Antennas and Propagation)
The prototype design and testing of an E band mmWave Time Modulated Array (TMA) is presented. The PCB based array has a 3 dB RF bandwidth of 71-73 GHz and a peak gain of −2 dBi on the first harmonic steered beam. The TMA second harmonic beam gain is within 0.9 dB of a conventional phase-shifter based array, in a like-for-like theoretical comparison. An array gain of +11.5 dBi is predicted for a full on-chip implementation. Good agreement between theoretical and prototype measured gains and array patterns are reported. Beam steering and phase correction are implemented using an FPGA, requiring only 2 digital lines per array element. A dedicated, bespoke GaAs mmWave Monolithic Integrated Circuit (MMIC) to realize the TMA is presented. A key feature of the MMIC is a sub 400 ps phase inversion switch. The MMICs provide a measured average gain of 4.4 dB and draw 61.2 mW. The TMA is demonstrated steering the first harmonic beam to +/−12 degrees and the second harmonic beam to +/−30 degrees. The maxim steer possible is +/−16 degrees for the first and +/−35 degrees for the second harmonic beams. The full hardware demonstrator platform is presented and laboratory measurements provided, confirming good operation of the array compared to theory. Our work is the first demonstration of a steerable TX TMA operating in E band.